STUDY AND PERFORMANCE OF PHOTOVOLTAIC CELLS WITH VARIOUS TYPE OF PARAMETER - Mahobia, S.K.; Kumrey, G.R.; Mahobia, Swati (International Journal of Engineering Technologies and Management Research, 2016)
Photovoltaic cells are converts about 15% of the solar energy falling into the useful electricity. The increase in the temperature increases the resistance of these cell and in turns decreases the cell efficiency. So, cooling these panels is the effective way of increasing the cell efficiency. The performance of the solar panel increases by reducing the temperature. This cooling is done by air cooling or water cooling on the self-designed modified panel. The solar panels are cooled by passing air with the help of blower.